1986
DOI: 10.1677/joe.0.1100341
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of exogenous and endogenous inhibin in sheep serum using a new and extremely sensitive bioassay for inhibin based on inhibition of ovine pituitary FSH secretion in vitro

Abstract: An extremely sensitive and reliable bioassay for inhibin based on inhibition of ovine pituitary FSH secretion in vitro was developed and used to measure exogenous and endogenous inhibin activity in the ewe. The sheep inhibin bioassay is 30- to 40-fold more sensitive than conventional rat inhibin bioassays. The minimum sensitivity of each bioassay in the measurement of inhibin activity in 1 ml of sheep serum is 220 mu. and 4080 mu. in the sheep and rat bioassays respectively. This sensitive inhibin bioassay has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 28 publications
5
47
0
1
Order By: Relevance
“…To investigate this possibility further, levels of immunoactive and bioactive inhibin were compared at various stages of the cycle. Immunoactive inhibin was quantified through use of an antibody directed against the a-subunit [7], and bioactivity was determined by inhibition of FSH production by ovine pituitary cells in vitro [24]. These two measures of inhibin were in general agreement at all times except after the LH surge, when apparent secretion of immunoactive inhibin was high but that of bioactive inhibin was low (unpublished results).…”
Section: Introductionmentioning
confidence: 89%
“…To investigate this possibility further, levels of immunoactive and bioactive inhibin were compared at various stages of the cycle. Immunoactive inhibin was quantified through use of an antibody directed against the a-subunit [7], and bioactivity was determined by inhibition of FSH production by ovine pituitary cells in vitro [24]. These two measures of inhibin were in general agreement at all times except after the LH surge, when apparent secretion of immunoactive inhibin was high but that of bioactive inhibin was low (unpublished results).…”
Section: Introductionmentioning
confidence: 89%
“…The assay cross-reacts with the free -subunit of inhibin but this has minimal effect on the measurement since the -subunit is present in low concentrations in peripheral blood of sheep . The sensitivity of the assay was in the range 40-80 pg 1-26 a-inhibin/ml plasma, or 80-160 mU equivalent of ovine follicular fluid standard (oFF CG1083) previously bioassayed in a sheep pituitary cell bioassay against an ovine testicular lymph standard with an arbitrary potency of 1 U/ml (Tsonis et al, 1986). The intra-and inter-assay CVs were 14-6% and 21-8% respectively based on quality control pools measured in 9 assays.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the rat, Muttukrishna & Knight (1991) described a stimulating action of inhibin on LH in sheep, whereas the effects on FSH were similar in these two species with a greater sensitivity of the sheep pituitary cells to inhibin (Tsonis et al 1986). The similarity of the effects of inhibin on FSH and LH as characterized by our rat and monkey pituitary cell culture systems underline the value …”
Section: Discussionmentioning
confidence: 58%
“…The main biological action of inhibin is the suppression of gonadotrophins, predominantly FSH, at the pituitary level. Since inhibin has become available in purified or recombinant preparations (Mason et al 1985a,b, Forage et al 1986, Mayo et al 1986), this effect on FSH has been proved in different in vitro systems of cultured pituitary cells of rats (Scott et al 1980, Farnworth et al 1988) and sheep (Tsonis et al 1986). Later, inhibin was administered in vivo to rats (Rivier et al 1991), sheep (Mercer et al 1987) and monkeys (Stouffer et al 1994) and the suppressive action on FSH confirmed.…”
Section: Introductionmentioning
confidence: 99%